Benzimentos: Estudo sobre a prática em São Miguel das Missões-RS. - Silva, Juliani Borchardt da (2014)
The job of blessing, practical and popular wisdom passed among generations, living culture represented and manifested in people´s daily lives facing the disposition of a community in order to fulfill their health problems or simply to listen stories, give advice and attention to those who looking for them in their homes, turned into small shrines where symbols, images, and mixed codes have meaning and consolidate the perceptions that they have of the world. Objects, prayers, words and notions of cure during the blessing given meaning, making memories and identities of people who share this practice in their everyday life. The research aims to study the practice of blessings in São Miguel das Missões (RS), to identify the profile of its practitioners, its main features, applicability, expressions, symbols, meanings and their transmission. Aspects related to their conflicts and relationships with religious institutions in the city are important elements analyzed during the research, as well as the process of 'touristification' by government agencies and entities associated with this segment, resulting in negotiations and reciprocals support of the parties which aim growth, status and legitimacy. The narratives produced by these agents were essential in the study and understanding of this practice being the only subsidy for its analysis and understanding today.